Pregnancy in the Obese Woman : Clinical Management - Conway, Deborah L. (Wiley-Blackwell, 2011)
Obesity is becoming an increasing global healthcare challenge, and overweight expecting mothers are at risk of complications during their pregnancy. This unique clinical focused book covers evidence-based practices for obstetricians and assists them as they care for both the fetus as well as the mother-to-be if a critical circumstance develops during the pregnancy.